Development Betawi Cultural Village Setu Babakan Tourist Destination Through Marketing Strategy Ass Add Value - Padri Achyarsyah; Rizki Nurul Nugraha; Dipa Teruna Awaloedin (West Science Interdisciplinary Studies, 2024)
This research focuses on the development of the Setu Babakan Betawi cultural village tourist destination through marketing strategies as an added value. The research will discuss the development opportunities of this tourist destination and highlight the approach to be taken, namely the marketing strategy to increase the added value of the destination. This research discusses the marketing strategy of artificial tourist destinations, such as the Setu Babakan Betawi Cultural Village Tourism Destination, is very important in the context of cultural heritage preservation and local economic development. This research can have significant positive impacts. First of all, the research can provide in-depth insights into the preferences, expectations and motivations of tourists visiting artificial tourist destinations. The object of this research is in the UN Setu Babakan in Srengseng Sawah Village. This research method uses qualitative with a SWOT analysis approach. This research aims to explore the marketing strategy of artificial tourist destinations, especially focusing on the Setu Babakan Betawi Cultural Village Tourism Destination. The results concluded that through the development of appropriate marketing strategies, this destination can become more attractive to various groups of visitors. The interactive experience that Setu Babakan offers through cultural, artistic, and culinary activities is its main strength